PENGARUH PEREMPUAN DALAM MENGENTASKAN KEMISKINAN: ANALISIS REGRESI PANEL WILAYAH PARIWISATA DAN NONPARIWISATA DI PROVINSI NUSA TENGGARA TIMUR, 2017-2024 - Kautsar Hilmi Izzuddin; Muhammad Dzaky Fawwaz (Badan Pusat Statistik Provinsi NTT, 2026)
Introduction: Nusa Tenggara Timur (NTT) consistently occupies a position as one of the provinces with the highest poverty levels in Indonesia. This situation is further worsened by poverty reduction targets that have not been met as of 2024, even though the region has great tourism potential. This poverty phenomenon is also closely linked to the economic participation of women. Background Problem: This study aims to analyze the impact of women on poverty and compare this effect between tourism and non-tourism areas in NTT. Novelty: While many studies on poverty have been conducted, research that compares the role of women by separating tourism and non-tourism bases in NTT remains very limited. Research Method: This study uses panel data regression analysis from 22 regencies during the 2017–2024 period, which also splits the model into tourism and non-tourism categories. Finding/Results: Results show that increases in women's life expectancy, expenditure, and literacy rates significantly lower poverty in tourism areas. However, in non-tourism areas, the labor force participation rate and literacy are the main factors, while life expectancy does not have a significant effect. On the contrary, the percentage of women of productive age does not show a significant impact in either region.